Un huis clos de papier. Du « Livret des Enfants-Assistés » à La Légende dorée. - Véronique Cnockaert (Flaubert: Revue Critique et Génétique)
This article focuses on Zola’s preparatory file for Le Rêve, in particular on the “Foundlings” file and a few folios devoted to Zola’s reading of Jacques de Voragine’s La Légende dorée, as well as on his knowledge of the articles “Child” and “Adoption” in the Grand Dictionnaire Universel of Pierre Larousse. Angélique’s identity is thus strongly supported by an administrative order (a student booklet) which will slowly become a spiritual and fictional order, as the young girl will increasingly detach herself (literally and figuratively speaking) from her identity booklet and dream her destiny through that of Saint Agnès. We will unravel the esthetic and poetic tensions, both in the preparatory file and the novel, created by this passage from the administrative to the legendary, that pulls the Naturalist novel towards a hagiographic scenario.